2021
DOI: 10.1186/s13256-021-03024-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical iron deficiency anemia with record low hemoglobin: a case report

Abstract: Background Anemia is a serious global health problem that affects individuals of all ages but particularly women of reproductive age. Iron deficiency anemia is one of the most common causes of anemia seen in women, with menstruation being one of the leading causes. Excessive, prolonged, and irregular uterine bleeding, also known as menometrorrhagia, can lead to severe anemia. In this case report, we present a case of a premenopausal woman with menometrorrhagia leading to severe iron deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
3
9
1
1
Order By: Relevance
“…Therefore, it is necessary to appropriately identify and treat high-risk patients with severe anemia. All three patients in the present study had a background of not seeking appropriate medical attention, which is in agreement with the existing literature (9,11,12). The cases of a socially vulnerable 42-year-old woman with a hemoglobin level of 1.4 g/dl (9), of a 21-year-old woman with mental retardation and a hemoglobin level of 1.7 g/dl (11) and of a 29-year-old woman with celiac disease and anorexia nervosa showing a hemoglobin level of 1.7 g/dl (12) were reported in 2021, 2013 and 2005, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it is necessary to appropriately identify and treat high-risk patients with severe anemia. All three patients in the present study had a background of not seeking appropriate medical attention, which is in agreement with the existing literature (9,11,12). The cases of a socially vulnerable 42-year-old woman with a hemoglobin level of 1.4 g/dl (9), of a 21-year-old woman with mental retardation and a hemoglobin level of 1.7 g/dl (11) and of a 29-year-old woman with celiac disease and anorexia nervosa showing a hemoglobin level of 1.7 g/dl (12) were reported in 2021, 2013 and 2005, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Cases of severe iron deficiency anemia complicated with uterine fibroids are not rare. However, only one case of severe anemia due to uterine fibroids with hemoglobin levels <2.0 g/dl has been reported to date (9). The present study reported three cases of life-threatening anemia with hemoglobin levels <2.0 g/dl caused by uterine fibroids and genital bleeding.…”
Section: Introductioncontrasting
confidence: 41%
See 1 more Smart Citation
“…A 45-year-old woman had an even lower hemoglobin level of 1.4 g/dL. Like our case, she was diagnosed with leiomyomas; however, she was unable to walk, with a history of a mechanical fall [ 14 ]. Another middle-aged woman with celiac disease complained of stomach discomfort and exhaustion [ 15 ].…”
Section: Discussionmentioning
confidence: 98%
“…There are other cases reporting critically low hemoglobin associated with AUB, but none of these patients had pancytopenia. A case of a 42-year-old woman with menorrhagia was reported with a hemoglobin of 1.4 g/dL but she was symptomatic with anemia, experiencing dizziness, fatigue and shortness of breath, and had normal platelet and white cell counts [ 9 ]. A case of a 21-year-old with AUB and a hemoglobin of 1.7g/dL was reported, but this patient was hemodynamically unstable with hypotension and tachycardia, and no associated pancytopenia [ 10 ].…”
Section: Discussionmentioning
confidence: 99%